Inbreeding depression in castor bean (Ricinus communis L.) progenies - Oliveira,Inocencio Junior de (2012)
The purpose of this study was to investigate inbreeding depression (DE) in castor bean. From a population derived from the Guarani cultivar, 60 mother plants were sampled. Three types of progenies were obtained from each one: from self-pollination (AU), from crosses (CR) and from open pollination (PL). Grain yield of the progenies was evaluated in two locations. There was a strong interaction of progenies x locations, which led to obtaining estimates within each location. Broad variation was observed in inbreeding depression, with mean values of 6.7% and 13.4%, comparing AU progenies with PL progenies. It was observed that the population has high potential for selecting promising inbred lines. The frequency of mother plants generating progenies with simultaneous high general combination capacity and low inbreeding depression was low. Recurrent selection will increase the occurrence of parent plants associating these two properties, which is necessary for obtaining superior synthetic varieties.